Skin microbiome considerations for long haul space flights - Caswell, Gabrielle; Eshelby, Ben (Frontiers in Cell and Developmental Biology, 2022)
Abstract Dysbiosis of the human skin microbiome has long been associated with changes to the pH of the skin, dermal immune function and chronic skin conditions. Dermatological issues have been noted as the most prevalent medical presentation in the microgravity environment of space. The change in gravitational forces has been implicated in human immuno-suppression, also impacted by changes in the gastrointestinal-skin axis and its impact on Vitamin D metabolism, altered microbial gene expression in resident flora (leading changes in biofilm formation) and increased virulence factors in potential pathogens. There are also other stressors to the skin microbiome unique to space travel, including increased exposure to radiation, prolonged periods of dry washing technique, air quality and changes in replication and growth parameters. Optimal microbiome health leads to enhanced skin barrier manufacture and maintenance, improved skin immune function and healing. In a microgravity environment expected to be experienced during long space flights, disruptions to the skin microbiome, coupled with increased virility of pathological viruses and bacteria has implications for holistic skin health, and is coupled with slowed rates of wound healing. Scenario management for holistic skin health and restoration of microbiome homeostasis on long space flights require consideration